Betting as Survival, Not Recreation: A West African Critique of Individualized Responsible Gambling Tools - Odionye, Chimezie Obinna (Critical Gambling Studies)

(untitled) (University of Alberta Library, 2026)
This commentary critiques the application of individualized responsible gambling (RG) tools, as advanced in recent psychological research by Michael J. A. Wohl and colleagues, within the context of Nigeria’s sports betting landscape. Drawing on their work on voluntary pre-commitment, feedback mechanisms like the Positive Play Quiz, and cognitive models such as the illusion of control, the piece argues that these interventions, rooted in Western recreational paradigms, function as a neoliberal veil in West Africa. In Nigeria, where youth unemployment rates are reported at around 23% amid economic crises (with official figures controversially lower at 6.5% due to methodological changes), betting is framed as a survival strategy rather than leisure. RG tools overlook structural drivers like poverty, aggressive fintech marketing, and capital extraction by global operators. With over 60 million Nigerians betting daily and the sports betting market projected at $1.64 billion USD in 2025 (rising to broader gambling revenues of up to $3.63 billion), harms extend beyond addiction to deepened inequality. The commentary calls for decolonizing harm prevention through structural reforms, including mandatory operator taxes specifically earmarked to fund local mental health research and indigenous gambling harm prevention studies. It urges a contextualized paradigm that prioritizes structural accountability and economic desperation over individual agency.